ANALISIS PENGAMBILAN KEPUTUSAN INCOTERMS PADA PENGIRIMAN SUKU CADANG DENGAN MODA TRANSPORTASI LAUT PADA PT XYZ - Rizka Nurfauziah; Thio Febrian; Roy Ferry; Muchammad Fauzi (LPPM Universitas Bina Bangsa, 2023)
PT. XYZ is a multinational company manufactured semi-finished raw materials of cocoa commodities. The continuity of the production process is very imporant in terms of ensuring that customers will receive a timely supply according to the schedule. The technology for processing the cocoa product in general is still produced by the oversea companies, especially from European countries. To support the production process, the procurement of spare parts for routine maintenance (preventive maintenance) plays an imporant role. Because procurement of the spare parts still involves the original equipment manufacturer company directly from the oversea company, the determination of incoterms will affect impor costs which will be borne by the seller or buyer depend on the agreement. These costs will also consider risk handling of impored the goods. Based on data obtained, the determination of incoterms at PT. XYZ in procuring spare parts for production machines still follows the incoterms proposed by the seller along with the submission of the price of spare parts. In this research, an analysis will be carried out on selecting the right incoterms based on incoterms 2020 covering aspects of cost and risk that can be used by PT. XYZ for making decisions to impor the spare parts in the next order.